Electrochemical formation of SnO2-SbxOy composition-modulated coating - Майзелис, Антонина Александровна; Байрачный, Борис Иванович (Technology audit and production reserves, 2015)
The results of the study of tin and antimony anodic oxidation in complex pyrophosphate-tartrate electrolyte are presented. The conditions of SnO2-SbxOy composition-modulated coating formation are described. Such coatings are formed in three steps. The first step is the deposition of underlayer of tin doped by antimony from the tin pyrophosphate-tartrate strike bath. The second step is the formation of tin-antimony composition-modulated coating that includes the alternating layers of alloy and mixture of metals and metal hydroxides in the pyrophosphate-tartrate electrolyte. The alloy is deposited at the low current density. The mixture of metals and metal hydroxides are deposited at higher current density. The third step is the electrochemical oxidation of composition-modulated coating under anodic polarization in the alkalized strike bath. The SnO2-Sb2O3 coatings may be used in the processes of catalytic oxidation of substances and energy devices.